Biomechanics of Running: Analyzing Gait for Enhanced Performance - Minh Quang Tran (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Running biomechanics, a multidimensional examination of human movement, emerges as a critical connection between science and sport. This study digs into the detailed gait examination, illuminating its far-reaching ramifications for athletes, coaches, and researchers. As runners move across the complex world of biomechanics, their gait transforms into a dynamic painting that reflects forces, movements, and structures. A full gait analysis unlocks the key to peak performance by detecting inefficiencies and correcting mechanics for increased speed and endurance. Aside from the goal of podiums, biomechanics emerges as a critical component in injury prevention. For determine the research used SPSS software and generate result included descriptive statistic, correlation coefficient, the regression analysis also that model summary between them. Gait analysis reveals possible danger factors, allowing runners to fix weaknesses and extend their running careers. The study continues with footwear innovation, in which shoes, guided by gait nuances, develop into personalized instruments that improve comfort and reduce injury risks. This research also emphasizes the collaborative character of biomechanics, which is a joint investigation among coaches, players, and researchers. A never-ending cycle of study and invention propels the field into unexplored territory. Wearable technologies and artificial intelligence-driven analysis are providing real-time feedback, altering how athletes approach training and competition as technology advances. Running biomechanics is a study of empowerment, accuracy, and constant progress. Each stride is a step ahead, not just in the quest for quicker times but also in the ongoing study of human potential. Overall result founded that positive and significant relation between biomechanics related to gait enhanced performance. This research captures the dynamic interaction between science and sport, encouraging more investigation into the complexities of human mobility and performance optimization.